ANALISIS KINERJA KARYAWAN PADA PT. PELABUHAN INDONESIA II (PERSERO) CABANG JAMBI - Wina Sundari (Jurnal Dinamika Manajemen, 2015)
In the current era of globalization, the human factor as a human resource is very important in an effort to achieve results in accordance with organizational goals. Therefore, to fulfill this goal, it is necessary to have good performance from each employee. To achieve this goal, a study was carried out to see the performance description of PT. Pelabuhan Indonesia II (Persero) Jambi Branch by using five performance factors which include Quality, Quantity, Cooperation, Accuracy and Creativity. The samples taken in this study amounted to 22 people consisting of four managers and fifteen supervisors. The data used are primary and secondary data. Data collection procedures were carried out by means of questionnaires, observations and interviews, while the analytical model used was descriptive. The results showed that the performance of PT. Pelabuhan Indonesia II (Persero) Jambi Branch is good. Of the five factors used, namely quality, quantity, cooperation, accuracy and creativity, it is known that the average of each factor is: the average quality factor is 4.37 indicating very good performance, the average quantity factor is 4, 13 indicates very good performance, the average cooperation factor is 4.31 indicating very good performance, the average accuracy factor is 3.92 indicating good performance, and the average creativity factor is 3.95 indicating good performance , this means that the five factors are in the very good and good range of scales.